Board diversity and firm performance: cases in sharia capital market of Indonesia - Sutrisno Sutrisno; Maslinawati Mohamad (Jurnal Siasat Bisnis, 2019)
The purpose of this study is to examine the effect of board diversity on corporate performance. In this paper, board diversity refers to the composition of board members consisting of women, foreign, ethnicity, size of the board of commissioner, and size board of directors. Whereas, corporate performance is measured by return on assets (ROA). The sample size of the study uses 48 publicly listed firms in the Sharia capital market of Indonesia for the observation period between 2015 and 2017. The results show that firms with women and foreigner in board had a significant and positive association with corporate performance. Similarly, the board of commissioners and the board of directors also had a significant and positive association with firm performance. However, the existence of the ethnic boards does not affect firm performance.